Adaptability Evaluation of White Haricot Bean (Phaseolus vulgaris L) Genotypes at the Eastern Amhara Regional State, Ethiopia - Mohammed, Awol Mohammed (Madda Walabu University Journal of Equity in Sciences and Sustainable Development, 2019)
An experiment conducted to identify and recommend widely adaptable and high yielder variety. Thirty genotypes with the standard check were evaluated in randomized complete block design with three replications at Sirinka, Chefa, Jari and Shewa robit for two years. Analysis of variance revealed highly significant differences (P<0.01) among the genotypes for all of the studied traits except number of seeds per pod. The mean grain yield performance ranged from 1630 to 3127kg ha-1. According to the result, genotype Bifort small seeded-15 scored the highest grain yield performance, 3127.9kg ha-1, followed by Navy line-40 and ZABR16574-37F-32 with average grain yield of 2929.7 kg ha-1 and 2857.3 kg ha-1, respectively. The combined analysis of variance showed significant difference for both main and interaction effects of genotypes and locations which led to exploit the significant effect of genotype by environment interaction. AMMI analysis was employed totally on six environments’ grain yield to assess the genotype and environment interaction to identify widely adaptable genotype. Based on variance and AMMI analysis on multi environment data, genotype Bifort small seeded-15 has the highest grain yield performance (3127.9 kg ha-1) and the most adaptable genotype. This genotype has 94.5% yield advantage overall countries’ haricot bean productivity. Therefore; Bifort small seeded-15 has been recommended for the tested and other similar haricot bean growing areas to increase production and productivity of this crop in the region.